ISLAMIC BANKING FINANCING AND ECONOMIC GROWTH: AN EMPIRICAL STUDY FROM INDONESIA - Muhammad Iryanto; Fathy Inat; Fadly S (IAIN Manado, 2020)
This research studies the relationship between Islamic bank financing and Indonesia's economic growth from 2017:1 to 2019:12. The analytical approach used is the Autoregressive Distributed Lag (ARDL) model, which can show the dynamics of short and long terms relationships. Also using the Granger causality test to study the relationship of causality between research variables. ARDL estimation results show the independent variable: Total Financing (TF), Mudharabah (PLS), and Murabahah (PMH) are proven to have long-term co-integration or in the long term move together in influencing Indonesia's economic growth (GDP). These three variables also have a dynamic short-term relationship with an adjustment speed of 52.47 percent per month. Furthermore, the Granger causality test results indicate that a supply-following relationship, economic growth affect the financing of Islamic banks in Indonesia. The vital record from this research is Islamic Banking intermediation empirically contributes directly to create economic growth justly, even though it still in a limited section.